Binarity Versus Magnetic Fields in Upper Main-sequence Stars - Hubrig, S. (2013)
We review the status of the work on the detection, possible origin, and modelling of magnetic fields in binary systems with intermediate- and higher-mass primaries at different evolutionary stages. This review also includes interesting findings on a few exotic systems.